Real-Time Image Processing using Flutter and Tflite Packages (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today’s world, the application available  in the field of real time image processing are slow, provide  results about a limited set of objects in a frame, and is not  easily usable by people of all age groups. The nature of  visual based knowledge is far better than anything else, if a  person wishes to know about an object, or to remember an  object, the best way is to first see how the object looks, and  vice-versa, if you know how the object looks and feels, and  you know what it is called, it would be best describable.  Applications like Google lens are already prevalent in the  market, but only available for android, which leaves rest of  the OS users in vain, creating a market space for the  untouched. Features like pose estimation can be inculcated  through different software to yield AI based solutions to  serve different purposes. Object detection and image  classification can not only provide you information about  the object, but in today’s connected world, can lead you to  different sources of knowledge for the same, be it a link to  buy the object, or a thesis about it or some facts about it.
Keywords: Object detection; Image classification; Pose estimation; Real-time image processing; Image processing; tflite; tensorflow lite; Flutter